LONG-TERM OPIOID THERAPY IN OLDER CANCER SURVIVORS: A RETROSPECTIVE COHORT STUDY - Shah, R (Innov Aging, 2018)
Opioid analgesics are key to optimal pain treatment in cancer patients. However, there have been growing concerns regarding long-term prescription opioid use in older cancer survivors, in part due to the worsening epidemic of opioid toxicity in the United States. This study examines the rates and predictors of prolonged opioid prescriptions (≥90-day supply/year) in older cancer survivors in Texas. We conducted a retrospective cohort study of 65,304 older cancer survivors (mean age: 77 years; ≥5 years post-diagnosis with no secondary cancer diagnosis or active anticancer treatment) and a sub-cohort of 43,376 opioid-naive cancer survivors diagnosed between 1995 and 2008 using the Texas Cancer Registry-Medicare linked database. Rates of prolonged opioid prescriptions were observed from 2008 to 2013, and the influence of patient-level characteristics on receiving a prescription were calculated with generalized estimating equations and presented as adjusted odds ratios. The percentage of cancer survivors receiving prolonged opioid prescriptions increased from 10.81% to 13.18% from the fifth year to the eleventh year post-diagnosis. An increase from 1.29% to 7.21% was seen in opioid naïve survivors. Increases were also seen for both cohorts after stratifying for breast, prostate, lung, and colorectal cancers. Statistically significant predictors of receiving a prolonged opioid prescription included length of survivorship, female gender, urban residence, disability as reason for Medicare enrollment, Medicaid eligibility, comorbidities, depression, and drug abuse. Our findings highlight the need for further work on the prescription patterns and efficacy of long-term opioid therapy in older cancer survivors. Supported by grants NIDA R01-DA039192 and CPRIT RP160674.